2015
DOI: 10.1037/pas0000074
|View full text |Cite
|
Sign up to set email alerts
|

Further clarifying prospective and inhibitory intolerance of uncertainty: Factorial and construct validity of test scores from the Intolerance of Uncertainty Scale.

Abstract: The Intolerance to Uncertainty Scale (IUS) was developed to measure a dispositional tendency to react negatively to uncertain events, regardless of the occurrence probability of those events. Recent evidence suggests a 2-factor structure underlying the IUS; 1 factor measuring a prospective aspect (i.e., desire for predictability) and the other assessing an inhibitory aspect (i.e., uncertainty paralysis). The factorial and construct validity of the IUS test scores among undergraduate students in Singapore were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(109 citation statements)
references
References 95 publications
(212 reference statements)
10
98
1
Order By: Relevance
“…More recent research has suggested that measures of IU should be designed around the specific situations in which they occur [1, 2, 44]. For example the items in the IUS-12 could be altered in future studies to make them specific to the diagnosis and treatment of lower back pain to improve our capacity to understand the role of IU in low back pain care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent research has suggested that measures of IU should be designed around the specific situations in which they occur [1, 2, 44]. For example the items in the IUS-12 could be altered in future studies to make them specific to the diagnosis and treatment of lower back pain to improve our capacity to understand the role of IU in low back pain care.…”
Section: Discussionmentioning
confidence: 99%
“…We chose the validated 12-question version (IUS-12) that utilises a 5-point Likert scale with responses ranging from ‘not at all characteristic of me’ to ‘entirely characteristic of me’ [1, 35–38]. Examples of questions included ‘unforeseen events upset me greatly’ and ‘the smallest doubt can stop me from acting’.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research (e.g., (Hong & Lee, 2015) has supported two robust dimensions of IU measurement, a more immediate behaviorally focused dimension (i.e., Inhibitory IU) and a more future-oriented cognitively focused dimension (i.e., Prospective IU).…”
Section: Running Head: Intolerance Of Uncertainy and Behavioural Decimentioning
confidence: 99%
“…One individual difference characteristic that seems to play a significant role in mental health and well‐being is intolerance of uncertainty (IU)—the inability to tolerate the idea that negative events may occur and cannot necessarily be predicted . High levels of IU have long been identified as a vulnerability factor for anxiety and depressive symptoms . The trait can further be separated into two components—inhibitory IU, characterized by a reduced likelihood of engaging in action due to uncertainty, and prospective IU, the form of IU linked to concerns and worries about the future .…”
Section: Introductionmentioning
confidence: 99%